IDENTIFYING THE TRAINING NEEDS AND THE KEY TRAINING TOPICS IN THE ENTERPRISES OF LATVIA - Zeide, Inga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The role of a workplace in the provision of lifelong learning processes is increasingly emphasised in the academic discourse. Since the early 21st century, a new term – “workplace pedagogy” (Billet, 2000) – has appeared, which signifies the increasingly important role of the workplace in the process of adult learning. The goal of this article is to discuss the key principles in determining the training needs and the key training topics in the enterprises of Latvia. The author of the article has carried out a qualitative study using a partially structured interview method. Four heads of human resource departments have been interviewed in four enterprises of Latvia with varied capital and with total number of employees reaching more than 6000. The outcomes of the study reveal three key tendencies in determining the training needs. First, the principle of urgency, namely, technical training, in order to ensure that corporate activities are pursued in accordance with law. Second, the principle of professional development for staff. This block contains various training options aimed at the development of the different skills and competences. Third, the training dictated by the development of information technologies. However, it must be noted that it is more characteristic to the enterprises specialised in information and communication technologies and thus could be integrated in the group mentioned in the second group. All the interviewees confirmed that training in the companies they represent is financially supported, although specific amount of expenditure was not mentioned. Still, it is possible to conclude that the planning and implementation of staff training form an integral part of corporate strategies. At the same time, it is possible to draw a conclusion that several crucial skills such as complex problem solving, cross-cultural competency, new media literacy, which have been mentioned as essential in the sources used for this research, have been neglected as staff training options.